Objective Conditions of Indonesian Language Learning in Improving Reading Comprehension and Writing Skills in Elementary Schools - Setiyadi, Ruli; Damaianti, Vismaia S; Hernawan, Asep Herry; Agustin , Mubiar (KnE Social Sciences, 2025)
This study aims to analyze the objective conditions of Indonesian language learning in improving reading comprehension and writing skills in elementary schools. The research method used is a case study with a qualitative approach. Data were collected through observation, in-depth interviews, and document analysis in five elementary. The results indicate that the Indonesian language learning process faces challenges in the form of a lack of variation in teaching methods and limited use of learning media. However, the use of a literacy-based approach and the provision of structured exercises can support the improvement of students’ reading comprehension and writing simple sentences skills. This study suggests the need to develop more contextual, innovative learning strategies to improve the quality of Indonesian language learning.